GYROSCOPIC MANAGEMENT AND GENERATION Y - Orhei Loredana; Bibu Nicolae; Vinke Joop (Annals of the University of Oradea: Economic Science, 2012)
In the professional field of business and management there is still little research done on the possibility if the Generation Y members (born between 1980 and 2000), which are the managers off the future, need a different approach in education and training to be prepared for the future. The authors will explain how a new didactical approach in business and management called â€œGyroscopic Managementâ€ can prepare these new managers to be of added value for the business. This specific approach was the start in 2007 of a specific (international) HRQM Bachelor study programme at Arnhem Business School, HAN University in the Netherlands. During this study programme, students are confronting this specific training and didactical approach with characteristics as self-reliance, self-study, and Socratic dialogue, ethical and â€œgyroscopicâ€ management. The programme has a clear vision and mission and didactical approach that triggers the above-mentioned elements. The approach focuses on the need for development of specific competencies like â€œIntercultural adaptabilityâ€, â€œInternational business awarenessâ€ and â€œSocial entrepreneurshipâ€ as added to the existing competencies needed for a Bachelor level in business and management education. As researchers, lecturers and trainers, the authors used and researched this approach during many lectures, seminars, trainings and workshops in the last years at Universities in Romania and The Netherlands. The authors present the characteristics of the members of the new Y generation and relate them to main elements of gyroscopic management as practice and the results of this practice for students. For this, the authors did a so-called â€œGrounded action researchâ€, from 2009 until 2012, among students of business and management studies. Further, the research was supported by focus groups over the same period. The authors have the opinion that this research is important because the new generation of managers seems to need different didactical approaches in education and training that fit better to their characteristics. The authors believe that this research can bring therefore added value to the field of management in the future.